Hungarian Monitoring, 12 July 1989 . [Magyar rádiófigyelő], 1989. július 12 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - How does the world see President Bush's visit? - Moscow Pravda sharply criticizes Baltic republic - Genscher's talks in Prague - Yeltsin attacks Gorbachev again Domestic Affairs: - Bush holds marathon series of discussions with Hungarian leaders and representatives of alternative organizations - In connection to funeral of János Kádár, László Rajk Jnr. initiates removal of his father's ashes from Kerepesi cemetery - Representatives of Austrian government and Hungarian opposition discuss Vienna-Budapest World Exposition today in Budapest Economy: - On National Bank's request, USD 50 million foundation established in US to finance capital investments in Hungary Külpolitika: - Miként látja a világ Bush elnök látogatását? - Élesen támadja a balti köztársaságot a moszkvai Pravda - Genscher prágai tárgyalásairól - Jelcin ismét támadta Gorbacsovot Belpolitika: - Bush maratoni tárgyalás sorozat a magyar vezetés tagjaival és az alternatív szervezetek képviselőivel - Kádár János temetése kapcsán ifj. Rajk László kezdeményezte, hogy születi földi maradványait áthelyezzék a Kerepesi-temetőből - A Bécs-Budapest világkiállításról tanácskozott ma Budapesten az osztrák kormány és a magyar ellenzék képviselői Gazdaság: - A MNB kérésére az Egyesült Államokban 5o millió dolláros pénzalapot hoznak létre a magyarországi tőke-beruházások finanszírozására